Determination of Photocatalytic Behaviour of ZnS for Dye Degradation - Patil , Bharati N. (New Trends in Physical Science Research Vol. 6, 2022)
Transition metal sulphides, particularly ZnS, have recently received a lot of attention due to its unique catalytic properties. ZnS is a promising material for different applications such as photocatalysts, photodetectors, gas sensors, piezoelectric sensors and ultraviolet lasers. Due to the rapid formation of electron–hole pairs by photo-excitation, these experiments have indicated that ZnS nanocrystals are good photo catalysts. It has been discovered that adding surfactant to the synthesis of ZnS causes a phase transition from cubic to wurtzite. ZnS is made in this study utilizing a hydrothermal technique using Ethylene diamine as a surfactant. X-ray diffractions (XRD), XPS, and UV/VIS spectra were used to evaluate the photophysical properties of the prepared sample. Photo catalytic breakdown of industrial waste under UV irradiation was used to determine the photo activity of produced ZnS with surfactant. The photocatalytic activity of ZnS without surfactant was also tested under the identical conditions. In comparison to ZnS without surfactant, ZnS with surfactant has greater catalytic activity.